Sustaining competitive advantage via business intelligence, knowledge management, and system dynamics - Quaddus, M. A.; Woodside, Arch G. (Advances in business marketing & purchasing ;, 2015)
Volume 22 includes two main chapters in both Part A and B. It appears in two parts because all chapters offer great depth in coverage of core issues senior executives must address for long-term survival of the firm: business intelligence, knowledge management, and understanding of the systems dynamics of interfirm behavior. In the first main chapter of Part A Azizah Ahmad demonstrates that high-performing firms must achieve useful on-going business intelligence (BI). Ahmad shows how plans are designed and implemented for viable BI operations. The main contribution of the study is the identification of the firm's internal resources of BI governance that influences successful BI deployment. In the second chapter Md Nuruzzaman shows how country risk, different political actions from the government, and bureaucratic behavior influence the activities in industry supply-chains in emerging markets. The outcomes of the study are useful for various stakeholders of the Bangladeshi RMG industry sector ranging from the government to various private organizations. The applications of this study are extendable through further adaptation in other industries and various geographic contexts.